Strengthening Nutritionist Competence in Community Health Centers as a Strategy to Address Stunting: A Descriptive Qualitative Study - Oktaviani Maun, Flaviana; Anindita, Rina (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2026)
Nutritionist competence constitutes a critical determinant of effective community nutrition services and plays a strategic role in stunting reduction at the primary health care level. Despite national efforts to reduce stunting prevalence, limited empirical evidence has examined how nutritionist competencies are enacted in routine practice within resource-constrained primary health care settings.This study aimed to explore and analyze nutritionist competencies in terms of knowledge, technical skills, and communication abilities in implementing stunting management programs at a primary health center in eastern Indonesia. A descriptive qualitative approach was employed using in-depth interviews, observations, and document review involving 11 participants: three nutritionist (female, aged 30-42 years), five mothers of children with stunting (female, aged 40-41 years), the head of the primary health center (male, 57 years), and two district level nutrition program managers (female, aged 32-36 years). The findings reveal that while nutritionist demonstrate adequate technical competence in anthropometric assessment and intervention delivery, gaps remain in participatory communication, digital data reporting consistency, and structured supervision mechanisms. Strengthening nutritionist competencies through integrated human resource management strategies, continuous professional development, and supportive organizational systems is essential to enhance the effectiveness of stunting reduction efforts in primary health care settings.